Drawing perspective methods for artists : 85 methods for creating spatial illusion in art - Boerboom, Peter, 1965-; Proetel, Tim (Rockport Publishers, 2017)
For laymen and professionals alike, this book offers a refreshing, simple approach to the graphic depiction of three-dimensionality.